Cross-country comparison of strategies for building consumer trust in food. (9th April 2019) - Wilson, Annabelle M; Tonkin, Emma; Coveney, John; Meyer, Samantha B; McCullum, Dean; Calnan, Michael; Kelly, Edel; O'Reilly, Seamus; McCarthy, Mary; McGloin, Aileen; Ward, Paul R
Summary: Consumer trust in the modern food system is essential given its complexity. Contexts vary across countries with regard to food incidents, regulation and systems. It is therefore of interest to compare how key actors in different countries might approach (re)building consumer trust in the food system; and particularly relevant to understanding how food systems in different regions might learn from one another. The purpose of this paper is to explore differences between strategies for (re)building trust in food systems, as identified in two separate empirical studies, one conducted in Australia, New Zealand and the UK (Study 1) and another on the Island of Ireland (Study 2). Interviews were conducted with media, food industry and food regulatory actors across the two studies ( n  = 105 Study 1; n  = 50 Study 2). Data were coded into strategy statements, strategies describing actions to (re)build consumer trust. Strategy statements were compared between Studies 1 and 2 and similarities and differences were noted. The strategy statements identified in Study 1 to (re)build consumer trust in the food system were shown to be applicable in Study 2, however, there were notable differences in the contextual factors that shaped the means by which strategies were implemented. As such, the transfer of such approaches across regions is not an appropriate means to addressing breaches in consumer trust. Notwithstanding, our data suggest that there is still capacity to learn between countries when considering strategies for (re)building trust in the food system but caution must be exercised in the transfer of approaches.